Marriage Registration in the Qur’an: Historical Insights and Contemporary Legal Relevance - Maulidia Mulyani (Legitima : Jurnal Hukum Keluarga Islam, 2024)
Purpose – Explicitly, the rules for registering a marriage in the Al-Qur’an are not explained. However, if we trace the text through historical and interpretive aspects, some texts refer to marriage registration. This research presents two questions related to the historicity of marriage registration in Islam, the texts of marriage registration in the Al-Qur’an and its legal relevance in the contemporary era. Methods – This qualitative analysis is based on library research data that traces the history and texts of the Al-Qur’an related to marriage registration. Findings – This research concludes several findings: First, legal regulations for marriage registration in Islam are rarely found, but texts have been found that have meaning, even though they do not lead to marriage registration, so interpretation is needed. Second, marriage registration is then carried out in law to provide protection within the scope of family law practice. Research implications – Marriage registration is needed as a form of protection in family law practice in Indonesia. The background of the Al-Qur’anic texts is not explained due to certain conditions in the past, but in the search, it is implied that recording something makes things easier.